Cannabis for the Treatment of Inflammatory Bowel Disease: A True Medicine or a False Promise? - Naftali, Timna (Rambam Maimonides Med J, 2020)
Cannabis is the most widely used recreational drug worldwide and is used by some patients with inflammatory bowel disease (IBD) to ameliorate their disease. Whereas epidemiological studies indicate that as many as 15% of IBD patients use cannabis, studies inspecting cannabis use in IBD are few and small. We have conducted several studies looking at the use of cannabis in IBD. In Crohn’s disease, we demonstrated that cannabis reduces the Crohn’s disease activity index (CDAI) by >100 points (on a scale of 0–450).Two small studies in ulcerative colitis showed a marginal benefit. However, no improvement was observed in inflammatory markers or in endoscopic score in either disease. Many questions regarding cannabis use in IBD remain unanswered. For example, cannabis is a complex plant containing many ingredients, and the synergism or antagonism between them likely plays a role in the relative efficacy of various cannabis strains. The optimal doses and mode of consumption are not determined, and the most common form of consumption, i.e. smoking, is unacceptable for delivering medical treatment. Cannabis is a psychotropic drug, and the consequences of long-term use are unknown. Despite all these limitations, public opinion regards cannabis as a harmless drug with substantial medical efficacy. In Israel, the number of licenses issued for the medical use of cannabis is rising rapidly, as are the acknowledged indications for such use, but good-quality evidence for the effectiveness of cannabis is still lacking. Further studies investigating the medical use of cannabis are urgently needed.